ANALISIS DAN EVALUASI PENGEMBANGAN RUTE BUS KAMPUS UNDIP DALAM RANGKA MENUJU TRANSPORTASI YANG BERKELANJUTAN - Murti, Redy Prasetyo Kresno; Hamivaldi, Mohammad Zulfikar; Ismiyati, Ismiyati; Supriyono, Supriyono (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
Diponegoro University (Undip) has a total of 67,000 students with high mobility resulting in congestion. Then Undip made an alternative by launching the Undep campus bus. The research aims to identify academic civitas perceptions of campus buses, evaluate campus bus performance based on minimum service standards (SPM), provide improvements in performance evaluation, and make recommendations to campus. The research uses mixed analysis methods, that is qualitative descriptive analysis with dissemination of questionnaires on academic citizens using campus buses as well as using quantitative methods with dynamic data surveys. Based on questionnaire results of identification of perceptions of academic civitas approving campus bus presence, evaluation of performance on physical buses there are 10 corresponding indicators of 20 indicators, bus route evaluation there are campus facilities that are not served and shelter evaluation results there are no information boards. So we need performance improvements to match the current SPM. The result of the recommendations to Undip campus is the development of routes, the need for efficiency of fleet operations at peak hours, improvement of information boards and shelters, repair of bus fleet, and integration of SIAP application with GPS tracking system. Then the development of campus bus routes is needed because there is a demand that has not been served so that more and more academic civitas are using campus buses and need advanced research on the vehicles operating costs (VOC).